Efficient and Precise Processing for Squinted Spotlight SAR through a Modified Stolt Mapping. (16th November 2006) - Vandewal Vandewal, Marijke Marijke; Speck Speck, Rainer Rainer; Süß Süß, Helmut Helmut
Abstract : Processing of squinted SAR spotlight data is a challenge because of the significant range migration effects of the raw data over the coherent aperture time. Although in theory the (ω, k )-algorithm takes care of these aspects, its digital implementation requires a time-consuming interpolation step. Moreover, the limited precision of this interpolation can introduce distortions at the edges of the final image especially for squinted geometries. A wave number domain processing using a modified Stolt mapping will be developed and analyzed to enhance the quality of the final SAR image. Additionally, the proposed algorithm has a decreased computational load compared to the original (ω, k )-algorithm. Simulation results will validate the focusing and efficiency performances of the modified wave number domain algorithm.